(NmETODY RAZWEDO^NOJ GEOFIZIKI(B. (NsEJSMI^ESKIE METODY IZU^ENIQ SLOVNODISLOCIROWANNYH SRED W RUDNYH RAJONAH (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NrABINOWI^(B, (NgRIGORIJ qKOWLEWI^s; "(NrUDGEOFIZIKA(B", (NNAU^NO(B-(NPROIZWODSTWENNOE OB(B-(NNIE (B((NlENINGRAD(B)s ((NlENINGRAD (B:s (Nnpo (B"(NrUDGEOFIZIKA(B",s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NrUDNYE MESTOROVDENIQs; (NsEJSMI^ESKAQ RAZWEDKAs